Manfaat Ratifikasi Statuta Roma dan Faktor-Faktor yang Menghambatnya - Amrullah, Irfan Maulana (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
The 1998 Rome Statute of the International Criminal Court (ICC) has been ratified by more than 120 UN member states to date. The establishment of the ICC is the result of the struggle of nations to form an international court for permanent serious human rights violations, including genocide, crimes against humanity, war crimes, and crimes of aggression. Unfortunately, although Indonesia is a signatory to the Rome Statute, it has not yet ratified it. The reason for the delay is concern that the ICC will replace national courts and prosecute national patriots on charges of serious human rights violations. This is an inappropriate reason because the ICC adheres to the principle of complementarity whereby national courts are the primary courts. The ICC also adheres to the principle of non-retroactivity, does not apply retroactively, and provides a 7-year deferral option and “opt-in” and “opt-out” options. As a result, ratification of the Rome Statute actually brings many benefits to Indonesia, especially strengthening Indonesia's position in the international community as a democratic country that supports world order, upholds independence, eternal peace, and social justice.